EKSISTENSI GOOD GOVERNANCE SEBAGAI PEMEDIASI ATAS HUBUNGAN ANTARA PROFESIONALISME DAN INDEPENDENSI DENGAN KUALITAS AUDIT - Maulidia, Oktoreza; Suratno, Suratno; Rachbini, Widarto (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
Audit Standard has been established to ensure the results of a quality audit. This study aims to determine the effect of professionalism and independence on audit quality with the mediation of good governance. In this research used survey method. The variables studied include the independent variables are professionalism and independence. The dependent variable is audit quality, and the mediation variable is good governance. Samples taken as many as 62 auditors at KAP Kanaka Puradiredja, Suhartono. The data was collected by questionnaire to measure the perception of the auditors regarding the variables tested. Processing techniques and data analysis with SmartPLS with Goodness of Fit Model equation model. The results of this study are: (1) Professionalism has no significant effect on audit quality (2) Professionalism has significant effect on audit quality through good governance as a mediator (3) Independence has significant effect on audit quality (4) Independence has significant effect on audit quality through good governance as a mediator.